Amphiphilic Poly(3-hydroxy alkanoate)s: Potential Candidates for Medical Applications. (21st February 2010) - Hazer, Baki
Abstract : Poly(3-hydroxy alkanoate)s, PHAs, have been very attractive as biomaterials due to their biodegradability and biocompatibility. These hydrophobic natural polyesters, PHAs, need to have hydrophilic character particularly for drug delivery systems. In this manner, poly(ethylene glycol) (PEG) and hydrophilic functional groups such as amine, hydroxyl, carboxyl, and sulfonic acid have been introduced into the PHAs in order to obtain amphiphilic polymers. This review involves in the synthesis and characterization of the amphiphilic PHAs.